Pengaruh Gaya Kepemimpinan dan Kerjasama Tim terhadap Kinerja Karyawan Pada Satuan Polisi Pamong Praja (Satpol PP) Kecamatan Cengkareng Kota Administrasi Jakarta Barat - Debi Rahmawati; NFH Ginting; Nurlelasari Ginting (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2024)
Impact of leadership style and teamwork on employee performance at Satuan Polisi Pamong Praja (Satpol PP) Subdistrit Cengkareng, West Jakarta. This is to find out about impact of the variabels for leadership style, teamwork and performance. The variables studied using questionnaire method from google form. Indirectly and the result managed by random sampling. The type of research used statistics test, data analysis test that using descriptive test, simple and multiple linear regression test, coefficient correlation and determination test. The next one, sample withdrawal technique that used is random sampling with 75 person of respondent. The results of this research showing that independence variabel have a positive impact and also significant for employees performance. Based on that, it shows us that leadership style (X1), teamwork (X2) and performance (Y) seems fcount 40,033 with 3,124 or 40,033 > 3,124 and the resulting of significant value is 0,000 < 0,05. It is conclude that leadrship style and teamwork having in employees performance at Satpol PP Subdistrit Cengkareng. Analysis result of multiple regression showing result value of coefficient determination in Adjusted Rsquare is 0,527 or 52,7%. It means leadership style and teamwork is simultaneously has an impact of 52,7% for performance, and 47,3% for the other factory which is not researched by this research.